2020
DOI: 10.1037/per0000367
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation and resting-state autonomic function in adolescent borderline personality disorder—A multimodal assessment approach.

Abstract: Borderline personality disorder (BPD) is characterized by persistent emotion dysregulation (ED), and ED is one of the core features of BPD. In recent years, research aimed to identify distinct patterns of ED characteristic of patients with BPD. These efforts comprised translational approaches, including psychophysiological measures. Autonomic nervous system (ANS) dysfunction, indexed by reduced resting-state heart rate variability (HRV), is suggested to be a psychophysiological marker of ED. Reduced HRV is see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In contrast, resting cardiac function, as indexed by heart rate (mixed sympathetic and parasympathetic influence) and vagally-mediated HRV was not altered in a study comparing outpatient adolescents with NSSI to healthy controls, although cardiac function was negatively related to symptoms of BPD (Koenig et al, 2017b). Greater severity of BPD pathology was also associated with increased heart rate and reduced HRV and these findings were recently replicated in an independent sample of adolescent patients (Weise et al, 2020). Additional analyses of Koenig et al (2017b) revealed that the relationship between resting cardiac function and dimensional personality pathology also held longitudinally (Koenig et al, 2018).…”
Section: Autonomic Nervous Systemmentioning
confidence: 88%
“…In contrast, resting cardiac function, as indexed by heart rate (mixed sympathetic and parasympathetic influence) and vagally-mediated HRV was not altered in a study comparing outpatient adolescents with NSSI to healthy controls, although cardiac function was negatively related to symptoms of BPD (Koenig et al, 2017b). Greater severity of BPD pathology was also associated with increased heart rate and reduced HRV and these findings were recently replicated in an independent sample of adolescent patients (Weise et al, 2020). Additional analyses of Koenig et al (2017b) revealed that the relationship between resting cardiac function and dimensional personality pathology also held longitudinally (Koenig et al, 2018).…”
Section: Autonomic Nervous Systemmentioning
confidence: 88%
“…Indeed, unaltered HRV has been proposed as a biomarker of self-regulation and mental health (Beauchaine and Thayer 2015 ). With regard to the aetiology of BPD, various results on reduced HRV point to a chronic reduction of the vagal ANS component, potentially reflecting a lack for efficient self-regulation (Thayer et al 2009 ; Koenig et al 2017 ; Weise et al 2020a , b ). Longitudinal studies suggest that changes in adolescent resting-state HRV are associated with changes in BPD symptomatology (Koenig et al 2018 ; Sigrist et al 2021 ), and even predicted clinical symptom reduction in adolescent BPD patients receiving dialectical behavioural therapy (Weise et al 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, adults with BPD have been found to show elevated testosterone levels when compared with healthy controls [36][37][38][39]. Further, there is evidence for greater resting-state HR and reduced restingstate vagally mediated HR variability (HRV) in adults and adolescents with BPD pathology [40][41][42][43]. To the best of our knowledge, no study today has investigated cortisol, testosterone, or HR in relation to aggressive behavior in adolescents with BPD.…”
Section: Introductionmentioning
confidence: 99%
“…t test with unequal variances. AQ, Aggression Questionnaire; BIS-11, Barratt Impulsiveness Scale; BMI, body mass index; BPD, borderline personality disorder; YPI, Youth Psychopathic Traits Inventory, CI, confidence interval; M, mean, SD, standard deviation.Cavelti et alPsychopathology 2022;55:[37][38][39][40][41][42][43][44][45][46][47][48] …”
mentioning
confidence: 99%